Anti-CCP Antibody and Rheumatoid Factor Positivity in a Case of Tuberculosis Arthritis - Murat Karkucak,; Erhan Çapkın,; Ömer Faruk Barçak,; Haşim Çakırbay,; Mehmet Tosun,; Ferhat Gökmen, (Archives of Rheumatology, 2010)
Tuberculosis (TB) can affect vertebras and joints bearing weight. It can resemble clinic signs, radiological and laboratory findings of rheumatoid arthritis (RA) involving peripheral joints. TB can make rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) positive, which are used in the diagnosis of RA arthritis. Therefore, this causes some difficulties in clinic diagnosis. Additionally, the diagnostic problems in TB arthritis can be more complicated. We aimed to attract attention to this situation by presenting a case of TB arthritis in which anti-CCP and RF are positive. (Turk J Rheumatol 2010; 25: 95-8)